Zavezništva in male države - Vegič, Vinko (Teorija in praksa, 1999)
Security of small states substantially depends on their reliance on external factors among which alliances are one of the possibilities for pursuing security. Bilateral alliance between small state and major power could produce negative consequences for small state since its subordination to the interest of major power. In multilateral alliances, like NATO, this possibility is slightly diminished. Currently the role of NATO and its activities are in the process of change because of increasing interdependence,integration, and enhanced role of institutions in Europe and some other part of the World and because of changing threats to security. Simultaneously the position of small states in NATO is being changed. With joining alliance states are always involved in dilemma between enhancing security and diminishing its autonomy. In the case that Slovenia in the future join NATO some positive security and political effects will emerge but also increasing liabilities and certain risks.
Keywords: mednarodno vojaško sodelovanje; NATO; mednarodna varnost; nacionalna varnost; obrambna politika; male države; Slovenia; Slovenija